A public awareness study about antibiotic consumption habits and antibacterial resistance in north-eastern region of Cyprus - Mehmet Ilktac; Mohammed Tamim Tarabishi; Pembe Ozbirtan; Canan Gulcan; Gulden Celik (Journal of Infection in Developing Countries)
Introduction: Antibiotic resistance is a current global issue. Investigation of the level of knowledge of the public about antibiotics and antibiotic resistance is necessary to combat the antibiotic resistance problem. The aim of the present study was to evaluate the level of knowledge of the citizens of the north-eastern part of Cyprus on antibiotics and antibiotic resistance problem.